Cultural Competence of EFL Students in Translating Idioms from English to Indonesian - Qoriatin Husnia Nurosida (Jetlal, 2022)
This study was going to discuss the cultural competence of EFL students and the strategies used to translate idioms by them since many previous studies discussed the translation of idioms, however they did not focus on how they are related to culture. The method applied of this study was descriptive qualitative to emphasize in explaining, describing, and understanding the context of the discussion. The results indicated that there were four strategies the learners used to transfer idioms, namely using idioms with the same meaning but different form, paraphrasing, omitting of a play on idioms, and omitting the entire idioms. Six of seven idioms could be rendered accurately by most of EFL students. Thus, they were considered as able to have cultural competence in translating idioms. The idiom itself is an expression whose meaning cannot be translated literally where they are affected by the cultural development of languages. A translator needs to have competence on culture to translate idioms, likewise EFL students who interact directly with translation activities.